2003
DOI: 10.2134/jeq2003.1809
|View full text |Cite
|
Sign up to set email alerts
|

Speciation of Phosphorus in Phosphorus‐Enriched Agricultural Soils Using X‐Ray Absorption Near‐Edge Structure Spectroscopy and Chemical Fractionation

Abstract: Knowledge of phosphorus (P) species in P-rich soils is useful for assessing P mobility and potential transfer to ground water and surface waters. Soil P was studied using synchrotron X-ray absorption near-edge structure (XANES) spectroscopy (a nondestructive chemical-speciation technique) and sequential chemical fractionation. The objective was to determine the chemical speciation of P in long-term-fertilized, P-rich soils differing in pH, clay, and organic matter contents. Samples of three slightly acidic (pH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
296
5
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 295 publications
(324 citation statements)
references
References 46 publications
19
296
5
4
Order By: Relevance
“…2f). This finding is in agreement with the generally accepted view that there is less adsorbed P in alkaline than in slightly acidic environments (e.g., Beauchemin et al 2003). Figure 2c,f shows that OCP and adsorbed P were the compounds that differed most significantly between slightly acidic and slightly Koerselman and Meuleman (1996).…”
Section: Discussionsupporting
confidence: 91%
“…2f). This finding is in agreement with the generally accepted view that there is less adsorbed P in alkaline than in slightly acidic environments (e.g., Beauchemin et al 2003). Figure 2c,f shows that OCP and adsorbed P were the compounds that differed most significantly between slightly acidic and slightly Koerselman and Meuleman (1996).…”
Section: Discussionsupporting
confidence: 91%
“…Surprisingly, the slopes of the regression lines between PSI and Mehlich 3 Al were not statistically different in the five different solution treatments (P , 0.05). It is not uncommon for metal oxides to play a strong role in P sorption in noncalcareous soils (Berkheiser et al 1980;Hsu 1964; Van der Zee and Van Riemsdijk 1986), though unlike our study most of these correlations have been observed with oxalate-extractable Al instead of Mehlich 3-extractable Al (Beauchemin et al 2003;Borggaard et al 1990;Borling, Otabbong, and Barberis 2001;Burkitt et al 2006;Kleinman and Sharpley 2002;Pierzynski et al 1990;Traina et al 1986). …”
Section: Phosphorus Sorption From Manurecontrasting
confidence: 72%
“…With pH values ranging from 8.0 to 8.3 for the swine effluent and Ca concentrations in excess of 50 mg L 21 , the precipitation of Ca phosphates may be one reason for the elevated DRP sorption observed for this solution. The greater PSI values observed for the CaCl 2 solution as compared to the KCl solution suggest that precipitation of Ca phosphates was also occurring in the CaCl 2 solution even though the pH in this solution only exceeded 6 in three of the soils, although Ca phosphates have been observed to form in soils with pH values less than 6 (Beauchemin et al 2003). The largest percentage difference in PSI values between the CaCl 2 and KCl solutions did in fact occur in the Lakin soil, which had the highest pH (6.5) value measured for the CaCl 2 solution.…”
Section: Phosphorus Sorption From Manurementioning
confidence: 89%
“…Results summarized in Table 3 are based on wide-range fits between -5 eV and 30 eV (relative energy) in first derivative space, implementing the described constraints. For these results, the sums of weighting factors on standards derived from the fitting result were subsequently normalized to 1 (14).…”
Section: Phosphorus Phases In Filter Samples As Shown By Xanesmentioning
confidence: 99%